Proximate Composition and In Vitro Bioactive Properties of Leaf Extracts from Seven Viola Species - Guangnian Zeng; Xingfan Li; Chunbo Zhao; Yongkang Pang; Xiongfei Luo; Zhonghua Tang (Foods)
Viola, an edible wild plant, is valued for its distinctive flavor and health-promoting properties. This study examines the proximate composition, bioactive compounds, and in vitro biological activities of seven Viola leaves (Viola prionantha, Viola collina, Viola acuminata, Viola variegata, Viola tokubuchiana var. takedana, Viola mirabilis, and Viola philippica). Findings reveal that the leaves of the seven Viola species are rich in phenolic compounds (131.13 mg gallic acid equivalents (GAE)/100 g fresh weight (FW)–384.80 mg GAE/100 g FW), flavonoids (13.09 mg rutin equivalents (RE)/100 g FW–40.08 mg RE/100 g FW), fatty acids (palmitic acid, linoleic acid, oleic acid, and α-linolenic acid), and essential minerals, such as potassium, calcium, and magnesium. The leaf extracts demonstrated significant inhibitory effects on α-glucosidase (84.17%) and pancreatic lipase (77.54%) at a concentration of 1 g of extract per milliliter of solution. Additionally, the biological activity of Viola leaves, particularly their antioxidant capacity, is associated with their phenolic and flavonoid content, with caffeic acid contributing up to 35.2% of the total phenolic acids and isoquercitrin being one of the most bioavailable flavonoids. These results indicate that Viola offers potential notable health benefits, presenting a valuable addition to enhancing modern dietary patterns and overall health.